Peran Motif Budaya dalam Cerita Rakyat Melayu dan Pengaruhnya Terhadap Identitas Kebudayaan Masyarakat - Desvia Mulya Putri; Nursalim Nursalim; Fitria Ananda; Khaisya Febio Zelvia; Nesha Ramadhini; Wulan Gustina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research examines the role of cultural motifs in Malay folklore and their impact on people's cultural identity. Malay folklore, with motifs such as mythological symbols, legendary figures, and traditional values, not only entertains but also strengthens the recognition and maintenance of cultural identity. Through a qualitative approach that combines text analysis and in-depth interviews, this research explores how these cultural motifs influence the construction of cultural identity, as well as their role in maintaining and developing local cultural heritage. The findings of this research highlight the importance of folklore in strengthening people's social and spiritual connections with their cultural environment.